Hubungan Emotional Intelligence dan Self-Esteem dengan Psychological Well-Being pada Siswa Kelas X SMAN 2 Klaten - Talangsih Eunike Waradanti; Selly Astriana (Humanitas (Jurnal Psikologi), 2025)
Adolescents in Indonesia often face various challenges, such as academic pressure, interpersonal relationship dynamics, and the influence of social media, which can affect their Psychological Well-Being . Several studies have shown that the majority of high school students in Indonesia have a moderate level of Psychological Well-Being . This study aimed to examine the relationship between Emotional Intelligence  and Self-Esteem on Psychological Well-Being  in 235 tenth-grade students at SMAN 2 Klaten. The study used a quantitative correlational approach with probability sampling through a cluster random method. Data were collected using three instruments: Ryff's Psychological Well-Being  Scale (Ryff, 1989), the Wong and Law Emotional Intelligence  Scale (WLEIS; Goleman, 1995), and the Rosenberg Self-Esteem Scale (Rosenberg, 1965). All instruments were tested for validity and reliability, with validity coefficients ranging from 0.35–0.72 and Cronbach's Alpha reliability >0.70, indicating adequate internal consistency. The results of the regression analysis showed that Emotional Intelligence  and Self-Esteem were positively and significantly related to Psychological Well-Being , both partially and simultaneously. These findings confirm that these two intrapersonal variables play a crucial role in supporting adolescent mental health. Therefore, it is recommended that schools and students develop emotional skills training programs and Self-Esteem strengthening programs through structured learning and counseling activities to optimally promote Psychological Well-Being Psychological Well-Being Psychological Well-Being Emotional Intelligence Self-EsteemPsychological Well-Being Emotional Intelligence Self-EsteemPsychological Well-Being Emotional Intelligence Self-EsteemPsychological Well-Being.